2017
DOI: 10.21767/2572-5394.100032
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Childhood Obesity with Education

Abstract: Background: Globally, childhood obesity is on the rise. It has more than quadrupled in adolescents since 1980. Childhood obesity has been linked with many chronic diseases. These diseases can decrease the life expectancy of the child. Our goal in nursing practice is to improve the care we provide, improve outcomes, and to educate the community on disease prevention. One way to positively impact the health of adolescents is by making an impression with our youth by teaching them how they can make healthy choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…The training was given to the individuals in the form of lectures on the principles of proper nutrition and exercises recommended by the American Heart Association, emphasizing the importance of health. Their results showed that the participants' test scores and overall knowledge improved after training,17 consistent with the present study results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The training was given to the individuals in the form of lectures on the principles of proper nutrition and exercises recommended by the American Heart Association, emphasizing the importance of health. Their results showed that the participants' test scores and overall knowledge improved after training,17 consistent with the present study results.…”
Section: Discussionsupporting
confidence: 92%
“…Blasingame17 conducted a study on 15 Spanish individuals aged 18 to 19 years to evaluate their knowledge gained through training. The training was given to the individuals in the form of lectures on the principles of proper nutrition and exercises recommended by the American Heart Association, emphasizing the importance of health.…”
Section: Discussionmentioning
confidence: 99%
“…4 One of the contributing factors to child obesity is a lack of education for children when it comes to making the right food choices and a lack of understanding of the consequences of those choices. 5,6 For example, distinguishing a healthy food option, such as a piece of fruit or vegetable, over food that is energy-dense and high in sugar, fat, and salt, and understanding the benefits of the healthy alternative are critical for a young child. 5 As food preferences can be established early in their life, consuming unhealthy foods in childhood can also result in poor food choices later on in life; trying to break that habit can be difficult for any child.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 For example, distinguishing a healthy food option, such as a piece of fruit or vegetable, over food that is energy-dense and high in sugar, fat, and salt, and understanding the benefits of the healthy alternative are critical for a young child. 5 As food preferences can be established early in their life, consuming unhealthy foods in childhood can also result in poor food choices later on in life; trying to break that habit can be difficult for any child. It is also important for children to make the right food choices, selecting healthier options rather than high-energy food with no nutritional value.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to distinguish food options and make healthy alternative choices in the prevention of nutritional disorders such as obesity. In the nutrition programs carried out in schools, solutions and materials are offered for wrong menu selection and bad eating habits that can cause obesity (Blasingame, 2017). In the study by McHugh et al (2019), it stated students who receive school health education have a good knowledge of the components of a healthy lifestyle and the importance of health for the future.…”
Section: Introductionmentioning
confidence: 99%